Watershed based drainage morphometric analysis using Geographical Information System and Remote Sensing of Kashmir Valley - KUMAR, ROHITASHW; ASHRAF, IFRA; KHAN, TANZEEL; HAMID, NYREEN; KHAN, J. N.; BHAT, OWAIS AHMAD; RAM, D. (Journal of Soil and Water Conservation, 2020)
Geographical Information System (GIS) has emerged as an efficient tool in delineation of drainage pattern of watershed, planning and management. GIS and image processing techniques can be employed for the identification of morphological features and analyzing properties of basin. The morphometric parameters of basin can address linear, areal and relief aspects. The present study was conducted to evaluate morphometric parameters of Wanpura micro-watersheds of Kashmir Valley. The morphometric parameters were determined to understand the nature, landscape development and hydrologic responses of watershed. Strahler’s stream ordering revealed a total 877 number of streams belonging to different orders with the highest order of 4. Drainage network of the basin was of dendritic type, which indicates the homogeneity in texture. The low value of drainage density (5.48) indicates that the region is composed of permeable sub-surface materials, dense vegetation and low mountainous relief causing lower surface runoff, and a lower level of degree of dissection. Low value of bifurcation ratio (1.79) shows that there is little control of structure on the drainage pattern. Low infiltration number value (0.0111 km/km4) indicates the high infiltration capacity of the soil which confirms to the huge vegetative cover of the watershed. This study would help to utilize the resources for sustainable development of the basin area